Simple Imperative Model Programming Language for Education – SIMPLE - Rababaah, Aaron (2020)
This work presents the development of a new programming language, Simple Imperative-Model Programming Language for Education SIMPLE. The new language is compiled procedural language that aims to simplify programming syntax and relives beginners from advanced programming concepts. SIMPLE was designed and implemented as a significant set of a typical procedural programming language. Although it is not intended for serious industry-level programming but, we claim that it could be an effective education vehicle and demonstrational component in introductory, intermediate and advanced courses. SIMPLE has been extensively tested using50+ different test programs designed carefully to target the language elements and features and our final tests showed that the language is reliable and ready to be adopted in education.